The trickle-down effect of leader psychological capital on follower creative performance: the mediating roles of job crafting and knowledge sharing - Karatepe, Osman M.; Ampofo, Emmanuel Twumasi; Kim, Taegoo Terry; Oh, Seokyoun (Emerald Group Publishing Ltd, 2024)
PurposeThe purpose of this study was to develop and test a research model that explored leader psychological capital (LPsyCap) as a predictor of follower creative performance (FCRP). The model also investigated follower job crafting (FJC) and follower knowledge collecting (FKC) and follower knowledge donating (FKD) behaviors as the multiple mediators of the trickle-down effect of LPsyCap on FCRP in a sequential manner.Design/methodology/approachData were obtained from hotel employees in Korea. The hypotheses were tested using structural equation modeling with the user-defined estimands function.FindingsLPsyCap boosted employees' FCRP. FJC and FKC behaviors mediated the trickle-down effect of LPsyCap on FCRP in a sequential manner. As predicted, FKC behavior parallelly mediated the effect of FJC on FCRP.Practical implicationsHotel firms should boost a workplace that would encourage employees to redefine and redesign their jobs. To achieve this, the presence of structural (e.g. learning new things in the workplace) and social (e.g. supervisor coaching) job resources and challenging job demands (e.g. willingly taking on additional tasks) would pay dividends.Originality/valueThis paper is one of its kind focusing on unexplored parallel and sequential multiple mediation effects that highlight FJC and FKC as the two potential mediators in the association between LPsyCap and FCRP.
Keywords: Trickle-down effect; Psychological capital; Job crafting; Knowledge sharing; Creative performance; Hospitality employees